2014
DOI: 10.1177/1088357614528797
|View full text |Cite
|
Sign up to set email alerts
|

High-Tech or Low-Tech? Comparing Self-Monitoring Systems to Increase Task Independence for Students With Autism

Abstract: Independence is the ultimate goal for students with disabilities, including secondary students with autism. One avenue targeted for increasing independence and decreasing prompt-dependency is through self-monitoring. In this study, investigators sought to determine whether a difference exists in levels of task independence when three students with autism complete food preparation tasks while self-monitoring using a low-tech treatment (paper/pencil) and high-tech treatment (iPad). Although both interventions de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 17 publications
1
71
0
Order By: Relevance
“…The alternative stimulus cues the individual and provides information regarding expectations related to the targeted behavior or skill (Hume et al, 2009). Self-monitoring has been shown to (a) increase independence (Bouck, Savage, Meter, Taber-Doughty, & Hunley, 2014;Hume et al, 2009), (b) decrease prompt dependency on an outside agent (Hume et al, 2014), (c) increase instructional time (Wehmeyer, Hughes, Agran, Garner, & Yeager, 2003), and (d) improve overall quality of life (Bouck et al, 2014;Lee, et al, 2007). Self-monitoring has also been shown to reduce the presence of problem behaviors and increase desired behaviors (Crutchfield, Mason, Chambers, Wills, & Mason, 2015;Zirpoli, 2012).…”
Section: Self-monitoringmentioning
confidence: 99%
“…The alternative stimulus cues the individual and provides information regarding expectations related to the targeted behavior or skill (Hume et al, 2009). Self-monitoring has been shown to (a) increase independence (Bouck, Savage, Meter, Taber-Doughty, & Hunley, 2014;Hume et al, 2009), (b) decrease prompt dependency on an outside agent (Hume et al, 2014), (c) increase instructional time (Wehmeyer, Hughes, Agran, Garner, & Yeager, 2003), and (d) improve overall quality of life (Bouck et al, 2014;Lee, et al, 2007). Self-monitoring has also been shown to reduce the presence of problem behaviors and increase desired behaviors (Crutchfield, Mason, Chambers, Wills, & Mason, 2015;Zirpoli, 2012).…”
Section: Self-monitoringmentioning
confidence: 99%
“…Digital interfaces, such as tablets, are relatively inexpensive and readily available within many classrooms, with the potential to reduce variability and enhance fidelity in a user-friendly manner (Kagohara et al 2013; see Almutlaq and Martella 2018;Cazaux et al 2019;Lorah 2018;Muharib et al 2019). Children on the autism spectrum can show a preference for interventions being delivered through tablet devices (such as iPads), compared to traditional methods (Bouck et al 2014;Mancil et al 2009; for systematic reviews of the benefits of iPads for autism interventions see Alzrayer et al 2014;Kagohara et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Future research might consider using similar systems programmed into tablets or the use of smartphones for portability, privacy, and independence (Crutchfield et al, ). As a case in point, Bouck et al () compared self‐monitoring with paper/pencil and with an iPad and found that students were more independent when using the iPad. Additionally, they found that from a social validity perspective, self‐monitoring on the iPad was preferred over paper/pencil (Bouck et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As a case in point, Bouck et al () compared self‐monitoring with paper/pencil and with an iPad and found that students were more independent when using the iPad. Additionally, they found that from a social validity perspective, self‐monitoring on the iPad was preferred over paper/pencil (Bouck et al, ).…”
Section: Discussionmentioning
confidence: 99%